Nuclear factor kappa B activation appears weaker in schizophrenia patients with high brain cytokines than in non-schizophrenic controls with high brain cytokines - Caitlin E. Murphy; Adam J. Lawther; Maree J. Webster; Makoto Asai; Yuji Kondo; Mitsuyuki Matsumoto; Adam K. Walker; Cynthia Shannon Weickert (Journal of Neuroinflammation, 2020)
Abstract Background High inflammation status despite an absence of known infection characterizes a subpopulation of people with schizophrenia who suffer from more severe cognitive deficits, less cortical grey matter, and worse neuropathology. Transcripts encoding factors upstream of nuclear factor kappa B (NF-κB), a major transcriptional activator for the synthesis of pro-inflammatory cytokines, are increased in the frontal cortex in schizophrenia compared to controls. However, the extent to which these changes are disease-specific, restricted to those with schizophrenia and high-neuroinflammatory status, or caused by loss of a key NF-κB inhibitor (HIVEP2) found in schizophrenia brain, has not been tested. Methods Post-mortem prefrontal cortex samples were assessed in 141 human brains (69 controls and 72 schizophrenia) and 13 brains of wild-type mice and mice lacking HIVEP2 (6 wild-type, 7 knockout mice). Gene expression of pro-inflammatory cytokines and acute phase protein SERPINA3 was used to categorize high and low neuroinflammation biotype groups in human samples via cluster analysis. Expression of 18 canonical and non-canonical NF-κB pathway genes was assessed by qPCR in human and mouse tissue. Results In humans, we found non-canonical upstream activators of NF-κB were generally elevated in individuals with neuroinflammation regardless of diagnosis, supporting NF-κB activation in both controls and people with schizophrenia when cytokine mRNAs are high. However, high neuroinflammation schizophrenia patients had weaker (or absent) transcriptional increases of several canonical upstream activators of NF-κB as compared to the high neuroinflammation controls. HIVEP2 mRNA reduction was specific to patients with schizophrenia who also had high neuroinflammatory status, and we also found decreases in NF-κB transcripts typically induced by activated microglia in mice lacking HIVEP2. Conclusions Collectively, our results show that high cortical expression of pro-inflammatory cytokines and low cortical expression of HIVEP2 in a subset of people with schizophrenia is associated with a relatively weak NF-κB transcriptional signature compared to non-schizophrenic controls with high cytokine expression. We speculate that this comparatively milder NF-κB induction may reflect schizophrenia-specific suppression possibly related to HIVEP2 deficiency in the cortex.